Prenatal Stress, Fearfulness, and the Epigenome: Exploratory Analysis of Sex Differences in DNA Methylation of the Glucocorticoid Receptor Gene - Ostlund, Brendan D.; Conradt, Elisabeth; Crowell, Sheila E.; Tyrka, Audrey R.; Marsit, Carmen J.; Lester, Barry M. (Frontiers in Behavioral Neuroscience, 2016)
Exposure to stress in utero is a risk factor for the development of problem behavior in the offspring, though precise pathways are unknown. We examined whether DNA methylation of the glucocorticoid receptor gene, NR3C1, was associated with experiences of stress by an expectant mother and fearfulness in her infant. Mothers reported on prenatal stress and infant temperament when infants were 5 months old (n = 68). Buccal cells for methylation analysis were collected from each infant. Prenatal stress was not related to infant fearfulness or NR3C1 methylation in the sample as a whole. Exploratory sex-specific analysis revealed a trend-level association between prenatal stress and increased methylation of NR3C1 exon 1F for female, but not male, infants. In addition, increased methylation was significantly associated with greater fearfulness for females. Results suggest an experience-dependent pathway to fearfulness for female infants via epigenetic modification of the glucocorticoid receptor gene. Future studies should examine prenatal stress in a comprehensive fashion while considering sex differences in epigenetic processes underlying infant temperament.